Building innovative competitive advantage in the minds of customers - (:unkn) unknown (Springer International Publishing, 2015)
The paradigm shifts of innovation and marketing in prior years have shown that these shifts arrive at a common point: competitive advantage. From the customers’ point of view, we recognize that brand associations are structured as a network in their minds and that customers distinguish among brands according to their competitive advantages. Therefore, a brand has innovative competitive advantage if it has strong favorable innovations associated with it in the minds of customers. These associations are created by innovating value that is strategically managed by marketers. Based on these concepts, the purpose of this study is to propose a conceptual model on innovative competitive advantage as a result of a detailed literature survey and a synthesis thereof. In addition, a pilot study follows the steps of brand concept mapping methodology, which enables us to represent brand image as a network of associations. It aims to demonstrate the practical application of brand innovativeness maps. © Springer International Publishing Switzerland 2015.